2021
DOI: 10.1002/app.50532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure induced by microcellular injection molding on electromagnetic interference shielding properties

Abstract: Preparing lightweight and versatile products is the unremitting goal of industry to save resources and energy. Lightweight carbon fiber reinforced polypropylene (CF/PP) composite foams with high‐performance electromagnetic interference (EMI) shielding materials were fabricated by microcellular injection molding (MIM) technology. The average length and distribution of CF in CF/PP composite foams were examined. Thanks to the introduction of foaming process, the average CF length of composite foams was 33.98% lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…19,20 However, so far only several studies reported the fabrication of carbon-based nanocomposite foams by using the FIM process, and the void fraction of those reported foams was at a low level (void fraction <50%). [21][22][23][24] Based on the researches, there may be two reasons that hinder the preparation of nanocomposite foams with high void fractions. First, carbonbased materials, such as carbon fiber, graphene and CNTs, exhibit outstanding intrinsic thermal conductivity.…”
Section: Demonstratedmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, so far only several studies reported the fabrication of carbon-based nanocomposite foams by using the FIM process, and the void fraction of those reported foams was at a low level (void fraction <50%). [21][22][23][24] Based on the researches, there may be two reasons that hinder the preparation of nanocomposite foams with high void fractions. First, carbonbased materials, such as carbon fiber, graphene and CNTs, exhibit outstanding intrinsic thermal conductivity.…”
Section: Demonstratedmentioning
confidence: 99%
“…FIM is one of the most important technologies in the foaming process because it can offer a lot of advantages, including better geometric accuracy, higher efficiency, lower cost, fewer residual marks 19,20 . However, so far only several studies reported the fabrication of carbon‐based nanocomposite foams by using the FIM process, and the void fraction of those reported foams was at a low level (void fraction <50%) 21–24 . Based on the researches, there may be two reasons that hinder the preparation of nanocomposite foams with high void fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the filler orientation significantly influences the electrical properties of conductive polymer composites, the degree of filler orientation corresponding to the highest electrical conductivity receives great attention, which helps to better regulate the electrical conductivity of micro/nanocomposites by adjusting the conductive filler orientation. Some studies reported that random filler orientation led to the highest electrical conductivity, , while others indicated that the highest electrical conductivity occurred at a higher filler orientation. In addition, conductive filler length also significantly affects the electrical properties of conductive polymer composites. Recent studies demonstrated that the filler length distribution had a non-negligible influence on electrical properties. , Since the SCF length distributes over a wide range in actual SCFCPCs due to the molding process, it is necessary to consider the actual SCF length distribution while analyzing the influence of SCF orientation on the electrical properties of SCFCPCs.…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the microfoaming parameters, the maximum EMI SE of 20 wt% CF/PP achieved 36.94 dB·cm 3 ·g −1 when the microcellular structure was optimal. [ 28 ] Obviously, the common optimization for filler dispersion in PP/MWCNT nanocomposites is microfoaming, and our research aims at using volume repulsion effect to optimize MWCNT conductive network, and then achieve high EMI SE.…”
Section: Introductionmentioning
confidence: 99%